2005
DOI: 10.1007/s11167-005-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Properties of Gel Films of Bacterial Cellulose

Abstract: The structure and sorption properties of gel films of bacterial cellulose were studied in its interaction with polyvinylpyrrolidone and silver nanoparticles stabilized by this compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
(14 reference statements)
0
8
0
1
Order By: Relevance
“…Moreover, it was also revealed that the (-110) crystallographic plane of the monoclinic cell of cellulose I β (d = 0.61 nm) is parallel to the plane of the sample. In this case, microfibrillar ribbons play the role of both a reinforcing network and hydrophilic layers that are capable of sorbing a large number of water and poly(vinylpyrrolidone) molecules or water-soluble silver and selenium complexes stabilized by poly(vinylpyrrolidone) on their surface [24,25]. The differences in the numbers and sizes of these nanocomplexes intercalated into the depth and at the surface of the cellulose Acetobacter xylinum gel films in the course of sorption were explained by the structural feature of the initial gel film, in which the microfibrillar ribbons consist of a large number of crystalline nanofibrils (subunits) having a cross section 13 × 7 nm in size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was also revealed that the (-110) crystallographic plane of the monoclinic cell of cellulose I β (d = 0.61 nm) is parallel to the plane of the sample. In this case, microfibrillar ribbons play the role of both a reinforcing network and hydrophilic layers that are capable of sorbing a large number of water and poly(vinylpyrrolidone) molecules or water-soluble silver and selenium complexes stabilized by poly(vinylpyrrolidone) on their surface [24,25]. The differences in the numbers and sizes of these nanocomplexes intercalated into the depth and at the surface of the cellulose Acetobacter xylinum gel films in the course of sorption were explained by the structural feature of the initial gel film, in which the microfibrillar ribbons consist of a large number of crystalline nanofibrils (subunits) having a cross section 13 × 7 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…3, curve 1) used for preparing the composite is similar to the structure of the classical hydroxyapatite Ca 5 (PO 4 ) 3 (OH). The analysis of the hydroxyapatite structure [29] shows that the presence of the hydroxyl groups and oxygen atoms of the (PO 4 ) 3-group, which are observed for different projections of the structure, is a necessary prerequisite for the formation of hydrogen bonds with a large number of hydroxyl groups and oxygen atoms at the surface of the (-110) and (110) faces of the crystal cellulose [24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for new nanoporous matrices for ferroelectric composites is going on together with attempts to improve the properties of existing nanostructured systems. Recently, to the traditional matrices (porous aluminum oxide, silicon and glass [1][2][3]) has been added chemically pure nanocrystalline cellulose (NCC) with unique sorption characteristics [4,5]. The sorption -desorption properties of nanocrystalline cellulose are conditioned by a large number of nanofibers with a width of 50-100 nm and a length, exceeding the width of a thousand and more times [4].…”
Section: Introductionmentioning
confidence: 99%
“…The sorption -desorption properties of nanocrystalline cellulose are conditioned by a large number of nanofibers with a width of 50-100 nm and a length, exceeding the width of a thousand and more times [4]. On crystal faces of these nanofibers arranged active primary ?=-groups, which are responsible for their high surface energy, that enables NCC to absorb a large number of water molecules as well as other water-soluble compounds [5].…”
Section: Introductionmentioning
confidence: 99%